2015
DOI: 10.1155/2015/838652
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Modulates a HER2-Associated Lipogenic Phenotype, Induces Apoptosis, and Increases Trastuzumab Action in HER2-Overexpressing Breast Carcinoma Cells

Abstract: In breast cancer, lipid metabolic alterations have been recognized as potential oncogenic stimuli that may promote malignancy. To investigate whether the oncogenic nature of lipogenesis closely depends on the overexpression of HER2 protooncogene, the normal breast cell line, HB4a, was transfected with HER2 cDNA to obtain HER2-overexpressing HB4aC5.2 cells. Both cell lines were treated with trastuzumab and docosahexaenoic acid. HER2 overexpression was accompanied by an increase in the expression of lipogenic ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 56 publications
(132 reference statements)
2
24
0
1
Order By: Relevance
“…The cell line that was most dissimilar from the other cell lines based on both PCA and dendrogram was SK-BR-3 cell line. SK-BR-3 is a representative of HER2 overexpressing tumor subtype that is known to have increased FASN activity resulting in increased lipid synthesis and changes in the lipidome [43,44]. The clustering verified that BC subtypes could be distinguished based on the lipidome and suggests that there is within-subclass variation in the lipidome.…”
Section: Plos Onementioning
confidence: 77%
“…The cell line that was most dissimilar from the other cell lines based on both PCA and dendrogram was SK-BR-3 cell line. SK-BR-3 is a representative of HER2 overexpressing tumor subtype that is known to have increased FASN activity resulting in increased lipid synthesis and changes in the lipidome [43,44]. The clustering verified that BC subtypes could be distinguished based on the lipidome and suggests that there is within-subclass variation in the lipidome.…”
Section: Plos Onementioning
confidence: 77%
“…Despite these data, there are no other reports describing the association of circulating FABP4 and breast cancer or even other cancer types. Furthermore, some recent publications have addressed the possible function of FABP4 in breast cancer , suggesting a putative role for this molecule in this pathology. These results are emerging with an exciting role for circulating FABP4 in breast cancer progression because circulating FABP4 would play a role in either fatty acid transport or activating key survival and proliferation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous FABP4 activates the cell proliferation of breast cancer cells and induces FABP5 and cluster of differentiation 36 (CD36) expression in MCF7 cells . Moreover, the overexpression of human epidermal growth factor receptor 2 (HER2) increases FABP4 levels , and FABP4 expression is high in HER2‐positive breast tumors . These results suggest a role for circulating FABP4 in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…HER2 over expression leads to up regulation of Bcl-2, Bcl-xL, Mcl-1, and suppresses p53-mediated apoptosis by up regulation of MDM2 and activation of AKT [35]. An in vitro study has indicated DHA inhibits HER2 activity and Akt signaling molecules leading to cell death [36].…”
Section: The Effects Of N-3 Pufas In Breast Cancermentioning
confidence: 99%